Recent Developments in Heck-Type Reaction of Unactivated Alkenes and Alkyl Electrophiles - Gao, Shuangqiu; Shi, Lili; Chang, Le; Wang, Binglin; Fu, Junkai (Synthesis, 2020)
The Mizoroki–Heck reaction is considered as one of the most ingenious and widely used methods for constructing C–C bonds. This reaction mainly focuses on activated olefins (styrenes, acrylates, or vinyl ethers) and aryl/vinyl (pseudo) halides. In comparison, the studies on unactivated alkenes and alkyl electrophiles are far less due to the low reactivity, poor selectivity, as well as competitive β-H elimination. In the past years, a growing interest has thus been devoted and significant breakthroughs have been achieved in the employment of unactivated alkenes and alkyl electrophiles as the reaction components, and this type of coupling is called as Heck-type or Heck-like reaction, which distinguishes from the traditional Heck reaction. Herein, we give a brief summary on Heck-type reaction between unactivated alkenes and alkyl electrophlies, covering its initial work, recent advancements, and mechanistic discussions.1 Introduction2 Intramolecular Heck-Type Reaction of Unactivated Alkenes and Alkyl Electrophiles2.1 Cobalt-Catalyzed Intramolecular Heck-Type Reaction2.2 Palladium-Catalyzed Intramolecular Heck-Type Reaction2.3 Nickel-Catalyzed Intramolecular Heck-Type Reaction2.4 Photocatalysis and Multimetallic Protocol for Intramolecular Heck-Type Reaction3 Intermolecular Heck-Type Reaction of Unactivated Alkenes and Alkyl Electrophiles3.1 Electrophilic Trifluoromethylating Reagent as Reaction Partners3.2 Alkyl Electrophiles as Reaction Partners4 Oxidative Heck-Type Reaction of Unactivated Alkenes and Alkyl Radicals5 Conclusions and Outlook
Keywords: Heck reaction; unactivated alkenes; alkyl electrophiles; carbon–carbon bond formation; radical chemistry